Overexpression of MutSα Complex Proteins Predicts Poor Prognosis in Oral Squamous Cell Carcinoma. Issue 22 (May 2016) - Wagner, Vivian Petersen; Webber, Liana Preto; Salvadori, Gabriela; Meurer, Luise; Fonseca, Felipe Paiva; Castilho, Rogério Moraes; Squarize, Cristiane Helena; Vargas, Pablo Agustin; Martins, Manoela Domingues
Abstract : Abstract: The DNA mismatch repair (MMR) system is responsible for the detection and correction of errors created during DNA replication, thereby avoiding the incorporation of mutations in dividing cells. The prognostic value of alterations in MMR system has not previously been analyzed in oral squamous cell carcinoma (OSCC). The study comprised 115 cases of OSCC diagnosed between 1996 and 2010. The specimens collected were constructed into tissue microarray blocks. Immunohistochemical staining for MutSα complex proteins hMSH2 and hMSH6 was performed. The slides were subsequently scanned into high-resolution images, and nuclear staining of hMSH2 and hMSH6 was analyzed using the Nuclear V9 algorithm. Univariable and multivariable Cox proportional hazard regression models were performed to evaluate the prognostic value of hMSH2 and hMSH6 in OSCC. All cases in the present cohort were positive for hMSH2 and hMSH6 and a direct correlation was found between the expression of the proteins ( P < 0.05). The mean number of positive cells for hMSH2 and hMSH6 was 64.44 ± 15.21 and 31.46 ± 22.38, respectively. These values were used as cutoff points to determine high protein expression. Cases with high expression of both proteins simultaneously were classified as having high MutSα complex expression. In the multivariable analysis, high expression of the MutSα complex was an independent prognostic factor for poor overall survival (hazard ratio: 2.75, P = 0.02). This study provides a first insight of the prognostic value of alterations in MMR system in OSCC. We found that MutSα complex may constitute a molecular marker for the poor prognosis of OSCC.